PENGARUH EKSTRAKURIKULER PRAMUKA TERHADAP KARAKTER KEPEMIMPINAN PESERTA DIDIK DI SMA NEGERI 1 INDRALAYA - Meidelasari; Sri Artati Waluyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Scout extracurricular activities on the leadership character of students at SMA Negeri 1 Indralaya. The leadership character is examined through five indicators: relationship-building, agility and adaptability, digital competence, broad insight, and acting as an agent of change. Employing a quantitative approach with a descriptive method, data were collected through questionnaires, interviews, and documentation. The population comprised 34 Scout members, all of whom were included as samples using a saturated sampling technique. The simple linear regression analysis revealed a positive and significant influence of Scout extracurricular activities on students' leadership character, with a coefficient of determination (R²) of 0,420 or 42%. This indicates that 42% of the variation in students' leadership character can be explained by their participation in Scout activities, while the remaining 58% is influenced by other factors. These findings suggest that Scout activities such as marching drills, routine training, and camping effectively foster practical and contextually relevant leadership values in students' daily lives.